Co(ii), Ni(ii), Cu(ii) and Cd(ii)-thiocarbonohydrazone complexes: spectroscopic, DFT, thermal, and electrical conductivity studies. Issue 60 (23rd November 2021) - Fouad, R.; Shaaban, Ibrahim A.; Ali, Tarik E.; Assiri, Mohammed A.; Shenouda, S. S.
Abstract : New and stable coordinated compounds have been isolated in a good yield. Abstract : New and stable coordinated compounds have been isolated in a good yield. The chelates have been prepared by mixing Co(ii ), Ni(ii ), Cu(ii ), and Cd(ii ) metal ions with (1 E )-1-((6-methyl-4-oxo-4 H -chromen-3-yl)methylene)thiocarbonohydrazide (MCMT ) in 2 : 1 stoichiometry (MCMT  : M 2+ ). Various techniques, including elemental microanalyses, molar conductance, thermal studies, FT-IR, 1 H-NMR, UV-Vis, and XRD spectral analyses, magnetic moment measurements, and electrical conductivity, were applied for the structural and spectroscopic elucidation of the coordinating compounds. Further, computational studies using the DFT-B3LYP method were reported for MCMT and its metal complexes. MCMT behaves as a neutral NS bidentate moiety that forms octahedral complexes with general formula [M(MCMT )2 Cl(OH2 )]Cl· X H2 O (M = Cu 2+ ; ( X = ½), Ni 2+, Co 2+ ; ( X = 1)); [Cd(MCMT )2 Cl2 ]·½H2 O. There is good confirmation between experimental infrared spectral data and theoretical DFT-B3LYP computational outcomes where MCMT acts as a five-membered chelate bonded to the metal ion through azomethine nitrogen and thiocarbonyl sulphur donors. The thermal analysis is studied to confirm the elucidated structure of the complexes. Also, the kinetic and thermodynamic parameters of the thermal decomposition steps were evaluated. The measured optical band gap values of the prepared compounds exhibited semiconducting nature. AC conductivity and dielectric properties of the ligand and its complexes were examined, which showed that Cu(ii ) complex has the highest dielectric constant referring to its high polarization and storage ability.